The Effect of Auditor’s Professional Skepticism and Whistleblowing System on Fraud Detection: Evidence from Indonesian Public Sector Audit - Amyar, Firdaus; Rahma, Almira; Azis, Nur; Suwarno, Suwarno (Research Horizon, 2023)
Fraud poses a pervasive and significant threat to organizations globally, with catastrophic consequences ranging from financial losses to reputational damage. This study investigates the roles of auditor professional skepticism and the whistleblowing system in combatting fraud and enhancing detection in investigative audits. Drawing from a comprehensive examination of 56 respondents in the Indonesian Supreme Audit Board, the study evaluates the validity and reliability of key research variables and tests three hypotheses. The findings indicate that, when analyzed individually, auditor professional skepticism does not significantly influence fraud detection. This aligns with prior research, emphasizing potential hindrances such as tight audit schedules and limited understanding of fraud perpetrators’ motives. Conversely, the whistleblowing system is found to have a significant and positive impact on fraud detection, with reliable information sourced from insiders aiding in early fraud identification. Moreover, when auditor professional skepticism and the whistleblowing system are combined, they synergistically enhance fraud detection significantly. These insights provide valuable guidance for organizations seeking to bolster their anti-fraud measures, underlining the importance of both elements in effective fraud prevention and detection efforts.